The new European regulation on personal data protection: significant aspects for data processing for scientific research purposes (Epidemiology, Biostatistics, and Public Health, 2022)
On 27 April 2016, after a troubled gestation,, Regulation 2016/6791 of the European Parliament and of the Council on the protection of natural persons with regard to the processing of personal data and on the free movement of such data was finally published.The Regulation is to have a two-year transitional period, meaning it will actually enter into force in the first half of 2018.